A new coal mine floor rating system and its application to assess the potential of floor heave. (April 2020) - Mo, Sungsoon; Ramandi, Hamed Lamei; Oh, Joung; Masoumi, Hossein; Canbulat, Ismet; Hebblewhite, Bruce; Saydam, Serkan
Abstract: Several underground coal mines have reported floor heave associated with the buckling mechanism. However, studies on the coal mine floor, especially the buckling failure mechanism in the floor and relevant analysis techniques, are still insufficient. This paper introduces a new floor classification system, the Coal Mine Floor Rating, based on the underlying failure mechanisms. The new floor mass rating system quantifies the stability of floor strata by considering two main factors: uniaxial compressive strength and discontinuity spacing of the floor units. The Coal Mine Floor Rating is incorporated into an empirical method, the Floor Heave Index, developed by statistical analysis of a database obtained from actual floor failure cases. The floor heave and non-floor heave cases are determined depending on the Coal Mine Floor Rating and the Horizontal Stress Rating, a proxy that represents the magnitude of horizontal stress. While obtaining underground floor data is challenging, the new floor classification system and the empirical method help assess the potential of significant floor heave on development in underground coal mine roadways for new mining projects or future workings.